Academic Academic Supervision: Academic Supervision - q, sy.faizah (Journal of Educational Management and Islamic Leadership (JEMIL), 2026)
Academic supervision is one of the essential instruments in improving the quality of education, particularly in guiding and developing teacher professionalism. In many educational institutions, especially in Indonesia, academic supervision is still often perceived merely as rigid administrative monitoring. In reality, its true essence lies in collaborative guidance aimed at enhancing the quality of teaching and learning. This study aims to describe how academic supervision significantly contributes to improving teacher competencies and the learning process. The research adopts a qualitative approach through a literature study method, collecting data from 20 relevant scientific references. The data were analyzed by identifying key themes, categorizing information, and interpreting interrelated concepts. The findings show that academic supervision has a positive impact on pedagogical competence, professionalism, and teacher motivation. Supervision models such as coaching, mentoring, clinical supervision, and ICT-based supervision have proven effective in creating a conducive working environment for improving the quality of teaching. Furthermore, the active involvement of school principals as supervisors plays a crucial role in the success of supervision to support educational transformation. This study concludes that academic supervision is not merely a control mechanism but a continuous development strategy that fosters a more professional, reflective, and innovative educational culture. Therefore, ongoing training and capacity building for supervisors are necessary so they can perform their roles optimally in supporting teachers toward high-quality learning outcomes.